Molecular characterization reveals no functional evidence for naturally occurring cross‐kingdom RNA interference in the early stages of Botrytis cinerea–tomato interaction. (28th September 2022) - Qin, Si; Veloso, Javier; Baak, Mirna; Boogmans, Britt; Bosman, Tim; Puccetti, Guido; Shi‐Kunne, Xiaoqian; Smit, Sandra; Grant‐Downton, Robert; Leisen, Thomas; Hahn, Matthias; van Kan, Jan A. L.
Abstract: Plant immune responses are triggered during the interaction with pathogens. The fungus Botrytis cinerea has previously been reported to use small RNAs (sRNAs) as effector molecules capable of interfering with the host immune response. Conversely, a host plant produces sRNAs that may interfere with the infection mechanism of an intruder. We used high‐throughput sequencing to identify sRNAs produced by B. cinerea and Solanum lycopersicum (tomato) during early phases of interaction and to examine the expression of their predicted mRNA targets in the other organism. A total of 7042 B. cinerea sRNAs were predicted to target 3185 mRNAs in tomato. Of the predicted tomato target genes, 163 were indeed transcriptionally down‐regulated during the early phase of infection. Several experiments were performed to study a causal relation between the production of B. cinerea sRNAs and the down‐regulation of predicted target genes in tomato. We generated B. cinerea mutants in which a transposon region was deleted that is the source of c.10% of the fungal sRNAs. Furthermore, mutants were generated in which both Dicer‐like genes ( Bcdcl1 and Bcdcl2 ) were deleted and these displayed a >99% reduction of transposon‐derived sRNA production. Neither of these mutants was significantly reduced in virulence on any plant species tested. Our results reveal no evidence for any detectable role of B. cinerea sRNAs in the virulence of the fungus. Abstract : Botrytis cinerea mutants lacking both Dicer‐like genes displayed a >99% reduction of transposable element‐derived small RNA (sRNA) production, but were not reduced in virulence, indicating redundancy of sRNAs in fungal virulence.